PENGARUH WAKTU AKTIVASI KIMIA PADA KARBON AKTIF BERBAHAN DASAR ARANG ROTAN SERTA KARAKTERISASI MENGGUNAKAN SEM DAN FTIR - Anita Carolina Waluyo; Satyano Mongan; Farly Tumimomor (Charm Sains: Jurnal Pendidikan Fisika, 2020)
Activation of rattan charcoal is carried out to increase pore size and formfunctional groups. In this study, activated carbon from rattan has been made withdifferent activation times. The research objective was to determine the pore size andfunctional groups contained in the activated carbon of rattan with an activation time of 5hours and 10 hours. The solution used to activate rattan activated carbon is KOH 10 mlcharcoal 10 grams with a burning temperature of 1500C. The results of rattan activatedcarbon were characterized using SEM and FTIR to see the pore size and functionalgroups. The activated carbon sample of rattan with the activation time of 5 hours had apore size that was not too large and only a few were formed and the sample of 10 hoursof activation time had a large pore size. The samples for 5 hours and 10 hours ofactivation have the same functional groups, namely O-H, C-C, C-O, C-H.